Inovace v České republice a Ruské federaci - Memekh, Darya (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Tato bakalářská práce se zabývá srovnáním inovativních aktivit zemí České republiky a Ruské federace. První část práce je představuje teoretické východisko o inovacích. Druhou část práce představuje analýza informací o České republice a Ruské federaci. Ve třetí části je uvedena srovnávací analýza faktorů obou zemí, které ovlivňuje vývoj inovací a určování inovačního potenciálu zemí. Poslední část práce obsahuje doporučení aktivit k podpoře inovací.

This bachelor thesis deals with the comparison of innovative activities of the countries of the Czech Republic and the Russian Federation. The first part of the work is based on the theoretical basis of innovation. The second part of the work is the analysis of information about the Czech Republic and the Russian Federation. In the third part, a comparative analysis of the factors of both countries that affect the development of innovation and determine the innovation potential of countries. The last part of the work contains recommendations for activities to support innovative activities.
Innovation in the Czech Republic and Russian Federation
Keywords: Inovace; inovační potenciál; inovační aktivity; Česká republika; Ruská federace.; Innovation; innovation potential; innovation activities; Czech Republic; Russian Federation.